2003
DOI: 10.1177/0146167203253474
|View full text |Cite
|
Sign up to set email alerts
|

Complementarity of Interpersonal Behaviors in Dyadic Interactions

Abstract: An important assumption of interpersonal theory is that during social interactions the behavior of one person tends to invite complementary behavior from the other person. Past research examining complementarity has usually used either confederates or fictitious interaction partners in their designs and has produced inconsistent results. The current study used observational ratings of behaviors of 158 participants as they interacted with partners across three different dyadic social situations. Randomization t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(118 citation statements)
references
References 29 publications
3
114
1
Order By: Relevance
“…A major tenet of interpersonal theory has been to formulate predictions about the expected directions of such covariation [17,37,42,51,58,72,73,88]. Thus, more specifically, with regard to dominance, the expected relation has been suggested to be one of oppositeness; greater dominance in one participant tends to invoke greater submissiveness in the co-participant, and vice versa.…”
Section: Interpersonal Theorymentioning
confidence: 99%
“…A major tenet of interpersonal theory has been to formulate predictions about the expected directions of such covariation [17,37,42,51,58,72,73,88]. Thus, more specifically, with regard to dominance, the expected relation has been suggested to be one of oppositeness; greater dominance in one participant tends to invoke greater submissiveness in the co-participant, and vice versa.…”
Section: Interpersonal Theorymentioning
confidence: 99%
“…In a number of studies, it has been found that when participants work on a task with either another participant or a confederate, they will display behavior that complements their partner's behavior (Locke & Sadler, 2007;Markey, Funder, & Ozer, 2003;Sadler & Woody, 2003;Strong et al, 1988;Tiedens & Fragale, 2003;Tracey, 1994). Further, the positive interpersonal consequences of dominance complementarity, suggested by interpersonal theory, have been documented in existing research.…”
Section: The Appeal Of Dominance Complementaritymentioning
confidence: 99%
“…Indeed, the notion of perceptions of dominance complementarity refers to a relationship between self and other perceptions. Therefore, almost all empirical work on complementarity assessed the existence of complementarity with an examination of the association between two individuals; positive correlations for the affiliation dimension and negative correlations for the dominance dimension were considered evidence of complementarity (e.g., Locke & Sadler, 2007;Markey, Funder, & Ozer, 2003;Sadler & Woody, 2003). For the most part, we used this same approach to capture perceptions of dominance complementarity.…”
Section: Overview and Empirical Approachmentioning
confidence: 99%
“…Interesting for future research would be to not only study the leaders' behaviours but also to examine the subordinates' reactions to these behaviours. Markey, Funder, and Ozer (2003) and Tracey, Ryan, and Jaschik-Herman (2001) show that when two persons interact their behaviours tend to conform to a circular pattern as predicted by the interpersonal circumplex. More importantly, their study demonstrates that dominant behaviours elicit submissive responses.…”
Section: Subordinatementioning
confidence: 94%